Controllable mortar spreader for floor tiling installation / Nur Arish Amanda Arbidin and Nor Azizah Talkis - Arbidin, Nur Arish Amanda; Talkis, Nor Azizah (2023)
Floor tiling is a prevalent and essential aspect of construction and interior design. The aim of the study is to develop a controllable mortar spreader robotic technology that can facilitate contract workers in achieving smoother the tiling installations, thereby preventing defects and promoting better health. The objectives of this study are to develop a prototype for floor tiling installation and assemble the prototype of the controllable mortar spreader for floor tiling installation, demonstrate its performance, and demonstrates its marketability potential for the people in the construction industry. Initial prototype tests were conducted to evaluate the system’s performance. The results indicated that the prototype can be improved by allowing for a considerably quicker installation process and allowing a less direct worker exposure to chemical products.